2012
DOI: 10.1364/oe.20.025255
|View full text |Cite
|
Sign up to set email alerts
|

Large-area semi-transparent light-sensitive nanocrystal skins

Abstract: We report a large-area, semi-transparent, light-sensitive nanocrystal skin (LS-NS) platform consisting of single monolayer colloidal nanocrystals. LS-NS devices, which were fabricated over areas up to 48 cm(2) using spray-coating and several cm-squares using dip-coating, are operated on the principle of photogenerated potential buildup, unlike the conventional charge collection. Implementing proof-of-concept devices using CdTe nanocrystals with ligand removal, we observed a substantial sensitivity enhancement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…[10] Owing to the single NC layer in the device structure, noise generation is significantly reduced, enhancing the device sensitivity. These PNSs offer the potential of high sensitivity for large-area applications as they operate on the principle of photogenerated voltage buildup in the absence of an external bias.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Owing to the single NC layer in the device structure, noise generation is significantly reduced, enhancing the device sensitivity. These PNSs offer the potential of high sensitivity for large-area applications as they operate on the principle of photogenerated voltage buildup in the absence of an external bias.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we reported that the highest possible sensitivity value for photosensitive NC skins is 104 mV under the illumination intensity of 0.175 mW/cm 2 at a 350 nm wavelength, and that their operating wavelength range is limited to 350–450 nm . Other recent work demonstrated that enhancing NC film absorption via plasmonic nanoparticles increases NC skin sensitivity .…”
Section: Introductionmentioning
confidence: 99%
“…During fabrication, the NC monolayers are dip‐coated with a computerized system on top of HfO 2 film. Synthesis of CdTe NCs and monolayer assembly procedures are all explained in detail in our previous works as well as in the experimental section here …”
Section: Introductionmentioning
confidence: 99%
“…These low-cost devices were initially operated on the basis of charge collection, where an electric field imposed on the detector dissociates the photogenerated excitons into electrons and holes, in which an electric current is produced [2]. On the other hand, as an alternative device structure, we have recently developed the light-sensitive nanocrystal skin (LS-NS) [3]. These LS-NS platforms, which were fabricated over areas up to 48 cm 2 , are operated on the basis of photogenerated potential buildup, as opposed to conventional charge collection.…”
mentioning
confidence: 99%